A Quality Study to Explore Rationale for Pregnant Women to Decline Transvaginal Cervical Length Screening. (15th May 2018) - Keller, Matthew; Burgess, Adriane; Hole, James; Warren, Margaret; Burkindine, Jessica; Johnson, Mary Jo
Abstract : Objectives: To identify patient rationale for pregnant women to decline transvaginal cervical length screening. Methods: Survey data from 511 women presenting for second‐trimester anatomy and transvaginal cervical length sonography were collected during a 4‐month period from September 2016 to January 2017. Each patient completed a medical questionnaire that includes demographic and obstetric history data and a survey to document their acceptance or declination of transvaginal cervical length screening. Results: Of the 511 women included in the study, 5.9% (n = 30) declined transvaginal cervical length screening. Demographic characteristics and risk factors for prematurity were similar between those who accepted and declined. The sonographer performing the study was significantly associated with declination of transvaginal cervical length screening ( P  < .001), with 4 of 13 sonographers accounting for 83.3% of all declinations. The most frequently reported reasons for declining the transvaginal cervical length screening were feeling that it was not needed (47%; n = 14) and not feeling prepared for the transvaginal sonography (27%; n = 8). Conclusion: The findings of this study indicate that the sonographer performing transvaginal cervical length screening may be associated with declination. The most common reasons patients cited for declining included not feeling that the study was needed and not feeling prepared for the procedure. Increased sonographer education and sonographer use of a scripted approach when discussing the procedure with patients may improve patient acceptance.